100 GHz Reflectometer for Sensitivity Analysis of MEMS Sensors Comprising an Intermediate Frequency Six-port Receiver - Linz, Sarah; Oesterle, Florian; Talai, Armin; Lindner, Stefan; Mann, Sebastian; Barbon, Francesco; Weigel, Robert; Kölpin, Alexander (IEEE Topical Conference on Wireless Sensors and Sensor Networks, 2015)
Due to the growing market for Micro Electro Mechanical Systems (MEMS), especially for the application in mobile electronic devices like cameras, phones or tablet computers, cost and time efficient test and evaluation systems are required for the production process. This work presents a novel measurement setup for MEMS microphones, that allows an inline, contactless evaluation of the microphones' mechanical sensitivity at an early stage of the manufacturing process. A heterodyne receiver with a Six-port demodulator is deployed for displacement detection with micrometer resolution. Since the Six-port demodulator allows very high sampling rates only limited by the analog-to-digital converter, short measurement times can be achieved.
elib2cris::1512001600,linz2015
Keywords: MEMS; Six-Port; Microwave Interferometer; W-band; Contactless Testing; Pull-in; Mechanical Sensitivity

A Large Deflection Model of Silicon Membranes for Testing Intrinsic Stress of MEMS Microphones by Measuring Pull-In Voltage - Oesterle, Florian; Fink, Franz; Dehe, Alfons; Kuhn, Harald; Weigel, Robert; Kölpin, Alexander (SPIE Microtechnologies, Smart Sensors, Actuators, and MEMS VI, Conference 8763, 2013)
Mechanical parameters, especially mechanical stress of membranes used in silicon microphones strongly depend on the manufacturing process. As a result, deviations during this process can result in sensitivity variations of the microphone. Therefore, the stress should be well controlled within a certain tensile level. This paper describes a method to test devices electrically using the MEMS related pull-in phenomenon with respect to the mechanical compliance of microphone membranes. Using this method, out of specification chips can be detected at an early stage within the manufacturing process instead of determination at a system functionality test after packaging. Therefore, the adequacy for the intended use of the pull-in voltage and its dependency on varying tensile stress due to manufacturing tolerance is evaluated.
elib2cris::1512001600,oesterle2013c
Keywords: Inspection equipment; Manufacturing; Microelectromechanical systems; Silicon

A New Approach on MEMS Sensor Batch Testing Using an Analogue Parallel Test Methodology for Massive Reduction of Test Time - Oesterle, Florian; Weigel, Robert; Kölpin, Alexander (IEEE Sensors, 2013)
With a tremendous shipment increase of MEMS microphones during the last few years, enhanced testing methods have become a key issue for industrial batch manufacturing, focusing on the mechanical sensitivity of the sound transducing diaphragm. Instead of semi-parallel techniques, in which test channels and measurement equipment are duplicated (with a multiplication of invest) for the purpose of further reduction of test time, this paper shows a novel approach for a massive parallel test of MEMS sensors. With several DUTs connected in parallel, the resulting measurements hence reveal several overlain device characteristics, each accounting for the sensitivity of one single DUT. For the specific correlation of those characteristics to each DUT, a reconstruction method known from tomography imaging techniques is adapted. The measurement results on wafer level shown in this paper exhibit the basic suitability of a single test of several DUTs in parallel and prove the concept of this novel method
elib2cris::1512001600,oesterle2013b
Keywords: MEMS; Parallel Testing; Mechanical Sensitivity; Pull-In; Microphone; Tomographic Reconstruction

A Novel, W-Band Microwave Based Contactless Test Method for Mechanical Sensitivity Analysis of MEMS - Oesterle, Florian; Vinci, Gabor; Weigel, Robert; Kölpin, Alexander (IEEE International Microwave Symposium, 2013)
The desired functionality of Micro Electro Mechanical Systems (MEMS) suffers from the influence on the nominal stress level of the mechanical components, e.g. by deviating manufacturing process parameters. Therefore, appropriate methods for testing mechanical parameters of MEMS is a key issue. The focus is on contactless techniques, short measurement time, accurate repeatability, and inline integration in manufacturing environments for mass production. Depending on the configuration of the device components, a couple of methods, such as optical interferometry, electrical impedance measurements and system level sensitivity tests are nowadays in use. This article presents a novel method for contactless testing of mechanical sensitivity of MEMS devices based on W-band microwave interferometry. Results of measurements at 90GHz are shown. The excellent detection of the test parameter verifies the feasibility and enormous potential of this proposed method.
elib2cris::1512001600,oesterle2013
Keywords: Microelectromechanical Systems; Contactless Testing; Microphones; Mechanical Sensitivity; Microwave Interferometry; W-band

Effizienzsteigernde Verfahren für den produktionsbegleitenden Test von MEMS-Mikrofonen - Oesterle, Florian (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2015)

Ein paralleles Verfahren zum Volumentest von kapazitiven MEMS Sensoren - Oesterle, Florian; Weigel, Robert; Kölpin, Alexander (26. ITG/GI/GMM-Workshop: Testmethoden und Zuverlässigkeit von Schaltungen und Systemen (TuZ), 2014)
elib2cris::1512001600,oesterle2014
Keywords: MEMS; Parallel Testing; Mechanical Sensitivity; Pull-In; Microphone; Tomographic Reconstruction

Evaluation of a Microwave Based Contact-Free Testing Method for Mechanical Sensitivity Analysis of MEMS for Inline Integration of On-Wafer Measurements - Oesterle, Florian; Gardill, Markus; Weigel, Robert; Kölpin, Alexander (Microwave Conference (EuMC), 2013 European, 2013)
Testing of Micro Electro Mechanical Systems is a key issue in high volume batch manufacturing. Deviating process parameters influence the nominal intrinsic stress level of the mechanical components, leading to a variation of the specified sensitivity, hence the system functionality. Focusing on a short test time, inline integration, and contactless excitation and analysis methods, establishing an electrical test for the required sensitivity within the mechanical domain is challenging. Depending on the design and functionality of the specific MEMS device, optical interferometry methods, Impedance or Network Analyzers or even final system level tests are implemented nowadays. This paper presents an alternative contactless testing method for sensitivity analysis of MEMS using microwave reflectometry. Proving the enormous potential of the method for inline integration, measurement results for varying chuck thickness and frequencies within the W-band are shown and evaluated, using a dedicated test setup for on-chip or on-wafer measurements.
elib2cris::1512001600,oesterle2013a
Keywords: MEMS; Mechanical Resonance; Mechanical Sensitivity; Contactless Testing; Microwave Reflectometry; Deflection Measurement; W-band; Microphone; Inline Integration

Six-Port Technology for Precise Geometrical Measurement Applications - an Overview - Kölpin, Alexander; Vinci, Gabor; Lindner, Stefan; Mann, Sebastian; Barbon, Francesco; Linz, Sarah; Oesterle, Florian; Weigel, Robert (European Microwave Conference (EuMC), 2013)
Instrumentation for precise geometrical measurements based on radar technology get more and more important for industrial applications. Besides distance, determining an angle or modal analysis of vibrations are key issues for automation in modern fabrication. Industrial applications put high demands on the measurement systems, not only regarding precision but also concerning operation in harsh environments and low cost implementations. In the last years Six-Port technology got more and more important for these applications. This paper will give an overview of Six-Port technique for geometrical distance measurements.
elib2cris::1512001600,koelpin2013b

Test Method for Contactless On-wafer MEMS Characterization and Production Monitoring - Linz, Sarah; Oesterle, Florian; Lindner, Stefan; Mann, Sebastian; Weigel, Robert; Kölpin, Alexander (IEEE Transactions on Microwave Theory and Techniques, 2016)
elib2cris::1512001600,linz2016

Ultra-Wideband Small Antenna Subarray Module with Narrow Elevation Pattern - Gardill, Markus; Schneider, J.; Oesterle, Florian; Fischer, Georg; Weigel, Robert; Kölpin, Alexander (IEEE-APS Topical Conference on Antennas and Propagation in Wireless Communications, 2013)
We propose an integrated small ultra-wideband antenna subarray module with narrow elevation pattern for future use in antenna arrays providing spatial processing capabilities such as Direction-Of-Arrival estimation in the azimuth plane, in the frequency range from 5 GHz to 8 GHz. The proposed subarray design is based on four mutually coupled Vivaldi antennas stacked on a common substrate in the E-Plane, with an element distance of delem 0;high=2. We optimize the antenna element in an infinite unit-cell stick array configuration and show that - in contrast to general believe - the truncation e ects when reducing the infinite stick-array to only four elements even reduce the total scan element reflection for broadside excitation. In addition, in contrast to most previously published E-Plane Vivaldi arrays, our design does not need a parallel-plate to microstrip balun at the feed point of each antenna element to realize an integrated planar feed network. Instead we use a novel ultra-wideband and geometrically small hybrid ring coupler to realize the array feed network directly in parallel plate technology, resulting in a low-cost, two-layer, single printed-circuit board integrated subarray module with narrow elevation pattern, operating from 5 GHz to 8 GHz.
elib2cris::1512001600,gardill2013e